Circadian pattern of Camponotus saundersi (Hymenoptera: Formicidae)in Tropical Rain Forest of Danum Valley, Sabah (Malaysia) - Mohd Afifi Ahmad Hamdan,; Mahadimenakbar,; Mohd Dawood,; Hairul Hafiz Mahsol,; Bakhtiar Effendi Yahya, (Pusat Sistematik Serangga ,UKM, 2013)

(untitled)
The exploding ant Camponotus saundersi is a rarely studied ant species especially their behaviour. This research mainly composes of observations of the workers' circadian patterns. Observations were made on three colonies of C. saundersi in Danum Valley, Sabah, Malaysia. A five day observation period was allocated on each of the colonies. The circadian pattern was observed by counting the number of individuals that enter and leave the nest for one minute each in the interval of 30 minutes. Workers of C. saundersi were observed to be active between 0400 and 1900 hrs daily. There were peaks of activities within the active period. However, one of the three colonies showed a slight longer activity.